1995
DOI: 10.1021/ma00128a033
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Scaling of Viscosity and Viscoelasticity of Polymer Solutions, Including Chain Architecture and Solvent Quality Effects

Abstract: This paper examines the dependence of polymer solution viscosity and higher viscoelastic parameters (e.g., y" Je°) on polymer concentration, molecular weight, chain architecture, and solvent quality. For solutions of linear chains, a transition from a solutionlike (stretched-exponential) to meltlike (power-law) dependence of on c or M occurs at [ ] » 1, and sometimes [ ] > 100. The hydrodynamic scaling description of polymer transport coefficients remains applicable to concentrations far above the overlap conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 15 publications
3
45
0
Order By: Relevance
“…Lin et al (14) found the same bifunctional behavior in high-molecular-weight poly-acrylic acid solutions. Similar transitions are found (15)(16)(17) in literature on solutions of some (not all) large-M polymers. In various systems, 4 ≤ φ + [η] ≤ 150, the intrinsic viscosity being [η].…”
Section: Rationalesupporting
confidence: 87%
See 1 more Smart Citation
“…Lin et al (14) found the same bifunctional behavior in high-molecular-weight poly-acrylic acid solutions. Similar transitions are found (15)(16)(17) in literature on solutions of some (not all) large-M polymers. In various systems, 4 ≤ φ + [η] ≤ 150, the intrinsic viscosity being [η].…”
Section: Rationalesupporting
confidence: 87%
“…The form was conjectured because (i) it is accurate (13)(14)(15)(16)(17) for another class of complex fluids whose dynamics are dominated by the forces (hydrodynamics, excluded volume) important here, and (ii) a known (18) ansatz leads to the form.…”
Section: Rationalementioning
confidence: 99%
“…Phillies notes that Eq. (1.106) is in agreement with experimental data for many polymer-solvent systems [Phillies, 1995;Phillies and Quinlan, 1995] and finds that the parameter α p varies with solvent quality as α p ∼ α 3 η = [η]/[η] θ , predicted by the hydrodynamic scaling model. Phillies further suggests [Phillies, 1995;Phillies and Quinlan, 1995] that the limit of applicability of Eq.…”
Section: Predictive Models For Solutions Of Flexible Neutral Polymerssupporting
confidence: 87%
“…Efforts have been made to model the viscometric behavior of polymer solutions through this entanglement transition. First, Phillies [Phillies, 1995[Phillies, , 2002aPhillies and Quinlan, 1995] has derived a pseudovirial expansion of the form Eq. (1.97), describing the concentration dependence of polymer solution viscosity by evaluating interchain hydrodynamic interactions to third order via an extension of the Kirkwood-Riseman model.…”
Section: Predictive Models For Solutions Of Flexible Neutral Polymersmentioning
confidence: 99%
“…Table IV contains data of eight researchers who studied rheological properties of four polar 36 that contain five adjustable constants). According to this equation, viscosity is a continuous function of polymer concentration and molecular weight.…”
Section: Asharementioning
confidence: 99%